The Influence of Destination Image on Tourist Revisit Interest in the Bogor Botanical Gardens - Siti Choerunisa; Rizki Nurul Nugraha (Westscience Press, 2024)
To create sustainable tourism, it is necessary to have an interest in returning to visit. One of the factors a tourist comes to visit again is influenced by several tourism factors, one of which is the image of the destination. This research was carried out at one of the tourist attractions in West Java province, namely the Bogor Botanical Gardens. In this study, SmartPLS was used using the SEM method. The results of the research show that destination image influences tourists' intention to revisit with an R-square of 71.7%.